In the lion's den [large type] - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- House of Falconer, 2021)
James Lionel Falconer has become the right-hand man of the head of London's most prestigious shipping company. Can James continue to be the master of his own fate, even after entering the lion's den?